Observations on the Implementation of Relationships, Sex, and Health Education (RSHE), Which Include LGBT Themes in an English Primary School - Alex Baird (Social Sciences, 2025)
The latest Relationships Education, Relationships and Sex Education, and Health Education (RSHE) Draft Guidance seeks to reduce the inclusion of LGBT themes in English schools. Additionally, the Gender Questioning Draft Guidance for Schools and Colleges and the Cass Review overlook the rights of trans and non-binary young people, further intensifying the heated debates surrounding their lives. In response, the author draws upon research conducted in a primary school in Greater London in 2021, when statutory RSHE, including LGBT content, was first introduced. The research aimed to understand how teachers felt about teaching RSHE and to collaborate with them to enhance pupil learning within and beyond the RSHE curriculum. This paper critiques lesson observations and teachers’ reflections on their lessons using a Framework for Sexuality Education and Queer Theory. The researcher’s call to rethink how RSHE is taught should not be taken to mean it should not be taught. To the contrary, the findings suggest a need for the school to broaden its curriculum, teaching methods, and strategies to become a truly ‘LGBT-inclusive’ environment. However, the paper also illuminates the apprehensions these primary school teachers experienced, which in turn influenced pedagogical decisions. The article concludes by recommending specific whole-school approaches and effective pedagogical practices for RSHE in the school, which could be beneficial to other primary school settings. Effective teaching of LGBT themes requires clear support for educators, especially within the complexity of a primary school setting and given the changing political and social climate.